Implementing Women's Leadership to Foster a Morning Dhikr Culture: Implications for Character Development and Motivation - Delis Ahlia; Hasyim Asy’ari (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to examine the role of women's leadership in fostering the culture of morning dhikr and its implications for character development and student learning motivation at SMK Yasiska Ciputat. Through a qualitative approach with observation, interview, and documentation techniques, this study found that inclusive and inspirational women's leadership is able to initiate significant changes in school culture. Morning dhikr activities are routinely proven to create a calmer learning atmosphere, increase discipline, and strengthen students' spiritual values. Dhikr also contributes to students' intrinsic motivation, fosters the spirit of learning, and encourages the desire to achieve. Female principals play a role model in shaping a religious climate that supports positive character and academic achievement. This research confirms that a combination of transformative leadership and strengthening spiritual culture can be an effective strategy in developing students' character and motivation in the school environment.